Urgensi Persistensi Laba : Antara Volatilitas Penjualan, Arus Kas Operasi, Tingkat Utang, dan Ukuran Perusahaan pada Perusahaan Manufaktur Sektor Barang dan Konsumsi yang Terdaftar di ISSI Periode 2016-2019 - Humayah, Sofiatun; Martini, Tina (AKTSAR: Jurnal Akuntansi Syariah, 2021)
The purpose of this study is to analyze and obtain empirical evidence on whether there is an influence between sales volatility, operating cash flow, debt level, and firm size on earnings persistence. This research is associative research with a quantitative approach. The technique used in sampling is purposive sampling. The data used in this research is secondary data. Furthermore, the data were analyzed using panel data regression analysis using the help of Eviews 10. The object of this research is a manufacturing company in the goods and consumption sector listed on the Indonesian Sharia Stock Index (ISSI) for the 2016-2019 period. The number of samples in this study was 15 companies. The results of this test partially debt level and firm size have a negative effect on earnings persistence. Meanwhile, sales volatility and operating cash flow have no effect on earnings persistence. The four independent variables have a proportion of 90.88% of their influence on the dependent variable and 9.12% is explained by other variables not included in the study.